Prevalence of the anti-CASPR2 autoantibody in patients with somatic symptom disorder accompanied by medically unexplained pain - Shingo Katayama; Gayatri Nayanar; Takayuki Suga; Motoko Watanabe; Chihiro Takao; Yojiro Umezaki; Hidehiko Takahashi; Akira Toyofuku; Hiroki Shiwaku (Brain, Behavior, & Immunity - Health)
Background: Medically unexplained symptoms (MUS) with pain are classified as somatic symptom disorder (SSD) with pain in the field of psychiatry, although an undetected biological basis may underlie at least some of these cases. One such candidate etiology is autoantibodies. Autoantibody etiologies are suspected in MUS with pain, including fibromyalgia, which is highly related to SSD accompanied with pain. Furthermore, autoantibodies against contactin-associated protein-like 2 (CASPR2) are known to induce neuropathy and pain, yet no study has examined the prevalence or clinical significance of anti-CASPR2 autoantibodies in patients with SSD accompanied with pain. Thus, the current study aims to investigate the seroprevalence of the anti-CASPR2 autoantibody among patients with SSD accompanied with pain and their associations with disease characteristics. Methods: The serum samples obtained from 264 patients with SSD accompanied with pain and 260 healthy controls were screened for anti-CASPR2 autoantibodies using a cell-based assay. Among the 264 patients enrolled, 231 with oral dysesthesia (including oral cenesthopathy) were assessed for clinical symptom severity using the Visual Analog Scale (VAS), Pain Catastrophizing Scale (PCS), and Somatic Symptom Scale-8 (SSS-8). Results: Of the 264 patients, 18 (6.8 %) tested seropositive for anti-CASPR2 autoantibodies. Among the 231 patients with oral dysesthesia, 12 (5.4 %) were positive for anti-CASPR2 autoantibodies. These patients with oral dysesthesia who were positive for anti-CASPR2 autoantibody reported significantly higher SSS-8 scores than those who were negative for autoantibody. Conclusion: Among patients with SSD accompanied with medically unexplained pain, a small subgroup was seropositive for anti-CASPR2 autoantibodies.